2019
DOI: 10.30659/e.4.1.87-100
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between self-efficacy and the duration of students� final project writing completion

Abstract: This study is aimed at finding out the relationship between self-efficacy and the duration of students' final project writing�commonly reffered as skripsi-completion. It was a correlational study involving 33 students of English Education and English Literature departments of the College of Languages and Communication Science of Sultan Agung Islamic University (UNISSULA) Semarang who were taken purposively as samples for the study. Data were collected by questionnaire of self-efficacy and a respondent-fill-for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Self-efficacy is also correlated to the length of time a student completed an academic product. The study of Rahmadini, which investigated students of English Education who were doing final project, found that there was a strong correlation between self-efficacy and the duration of final project completion (Rahmadini, Hartono, & Rohmaniyah, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Self-efficacy is also correlated to the length of time a student completed an academic product. The study of Rahmadini, which investigated students of English Education who were doing final project, found that there was a strong correlation between self-efficacy and the duration of final project completion (Rahmadini, Hartono, & Rohmaniyah, 2019).…”
Section: Introductionmentioning
confidence: 99%